Implementasi Budaya Organisasi di SMK Nurul Huda Al - Gina Cimerak - Nuryadin Nuryadin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
This study aims to describe how the implementation of organizational culture in SMK Nurul Huda Al Gina Cimerak. The type of research used is qualitative research. Data collection techniques used include observation, interview, and document study techniques. The results showed that the form of organizational culture at SMK Nurul Huda Al Gina Cimerak emphasized on four things: discipline, leadership cooperation, and efficiency and effectiveness. Each component has shown quite good results. The school faces a number of challenges in implementing the organizational culture activity program, namely the school's internal resources including the shortage of teachers in certain fields such as scouting and computers. In addition, teachers do not provide proper instruction on literacy in the classroom. One of the factors that hinders the effective implementation of Islamic school culture is also an inhibiting factor in implementing organizational culture. In the field of education, the presence of a flexible organizational culture is becoming increasingly important in the highly dynamic era of globalization, which has a significant impact on the future of the company. In a good school organization, it is expected that tasks and responsibilities are evenly distributed throughout the organization according to their capacity and function.